2017
DOI: 10.15376/biores.13.1.220-230
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Xylanase from Spent Mushroom Compost and its Application in Saccharification of Biomass Wastes

Abstract: The activities of xylanase extracted from spent mushroom composts (SMCs) of Coprinus comatus, Auricularia auricular, Pleurotus ostreatus, Pleurotus citrinopileatus, Agrocybe cylindracea, Hericium erinaceus, Hypsizygus marmoreus, and Tremella fuciformis were investigated. The crude extract from T. fuciformis SMC showed high xylanase activity with a value of 255.2 U/mg. Furthermore, this xylanase was purified using a combination of ammonium sulfate precipitation, diethylaminoethylcellulose (DEAE-cellulose), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 20 publications
3
9
1
Order By: Relevance
“…5). Several studies report that the presence of ion Ca 2+ in concentrations between 1 to 10 mM plays an important role on enzyme function and stability corroborating with the effect observed in AFUMN-GH10 and xylanases from P. citrinum [47] , Tramella fuciformis [55], A. niger [56] and Xanthomonas axonopodis pv. citri [49].…”
Section: Resultssupporting
confidence: 58%
“…5). Several studies report that the presence of ion Ca 2+ in concentrations between 1 to 10 mM plays an important role on enzyme function and stability corroborating with the effect observed in AFUMN-GH10 and xylanases from P. citrinum [47] , Tramella fuciformis [55], A. niger [56] and Xanthomonas axonopodis pv. citri [49].…”
Section: Resultssupporting
confidence: 58%
“…(P. florida, P. ostreatus, P. flabellatus, and P. pulmonarius) ranged from 304.4 ± 3.1 to 486.7 ± 3.6 U/mg. Maximum activity of xylanase was observed from SMS of P. pulmonarius (486.7 ± 3.6 U/mg) which is significantly higher than that in the earlier reports by Lin et al [39] which showed the highest xylanase activity of 255.2 U/mg in the SMS extract from Tremella fuciformis. Among the Pleurotus spp.…”
Section: Discussioncontrasting
confidence: 65%
“…Fungal laccases are reported to have wider industrial applications, such as decolorization, detoxification, bleaching of pulps, removal of phenolics from wine, and in biosensor manufacturing [38]. Xylanase is a crucial factor in determining the hydrolysis effectiveness of cellulolytic enzyme complex [39]. Recently, xylanase has received substantial industrial interest as a supplement in ethanol and xylitol production, in animal feed, for manufacturing of bread and alcoholic beverages, and bleaching of cellulose pulps in textiles [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the enzymes synthesized by the fungi Humicola lanuginosa, Mucor corymbifer and Mucor pusillus open up new perspectives for the use of their enzymes in various biotechnological processes, especially in the bioconversion of plant waste (14,20) because, their enzymes systems are balanced by the activity of all enzymes catalyzing the main polymers that including in the composition of plant waste.…”
Section: Resultsmentioning
confidence: 99%